2014
DOI: 10.1093/ckj/sfu120
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and body fat are predictors of hypovitaminosis D in renal transplant patients

Abstract: BackgroundHypovitaminosis D has been frequently reported after renal transplantation, but the impact of obesity and other factors in the reduction of vitamin D levels is not well established. We aimed to evaluate risk factors contributing to hypovitaminosis D among nondiabetic renal transplant recipients (RTR) with serum creatinine <2.0 mg/dL, at least 6 months after transplantation.MethodsOne hundred RTR were subjected to anthropometric evaluation and body composition assessment through bioelectrical impedanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…Weight gain during the 1st year post-tx was significantly higher in the vitamin D-deficient group in the present study. Similar findings were observed by Baxmann et al (36) in RTR. Several mechanisms have been proposed to explain the lower levels of 25(OH)D in obese individuals, and the main mechanism appears to be the sequestration of vitamin D by adipose tissue (51) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Weight gain during the 1st year post-tx was significantly higher in the vitamin D-deficient group in the present study. Similar findings were observed by Baxmann et al (36) in RTR. Several mechanisms have been proposed to explain the lower levels of 25(OH)D in obese individuals, and the main mechanism appears to be the sequestration of vitamin D by adipose tissue (51) .…”
Section: Discussionsupporting
confidence: 91%
“…Some studies conducted in Brazil also found that more than half of the participants presented hypovitaminosis D. These studies included the general population (32,33) and chronic kidney disease (CKD) patients in predialysis (34,35) . In Brazil, to date, only one study evaluated the prevalence of hypovitaminosis D in RTR (36) , and was conducted in the city of São Paulo, which has a higher latitude (23°32'51"S) than Rio de Janeiro, and the prevalence of hypovitaminosis D was higher (65 %). As expected, the prevalence of vitamin D deficiency/insufficiency in the present study was lower than that observed in previous studies conducted with RTR in other countries with higher latitudes (12)(13)(14)(37)(38)(39) .…”
Section: Discussionmentioning
confidence: 99%
“…Hypovitaminosis D was more prevalent for patients who had their blood samples drawn during winter, as already evidenced in our country (29, 30). Some studies have reported an association between hypovitaminosis D with BMI (29, 31) possibly due to either the low exposure of obese individuals to sunlight or sequestration and storage of vitamin D in adipose tissue (32). We did not observe a higher BMI, waist circumference or percentage of body fat in vitD-insufficient patients, differing from previous studies by our group and others in CKD or after renal transplant (29, 31), but corroborating with Gronborg et al (33), who found no association.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has been suggested that vitamin D deficiency was associated with an increased risk of developing obesity in subjects who were non-obese (13) . Inversely, obesity appeared to be a risk factor for hypovitaminosis D in nondialysed patients with chronic kidney disease and in renal transplant patients (14,15) . Taken together, these studies have highlighted a strong link between MetS, obesity and hypovitaminosis D.…”
Section: Introductionmentioning
confidence: 98%